KOMPOR EKONOMIS BERBAHAN BAKAR OLI BEKAS (Department of Mechanical Engineering, Faculty of Engineering, Universitas Negeri Semarang, 2022)
This study aims to determine the design of a stove (burner) fueled by used oil, along with its specifications and to find out the test results using a stove (burner) burning used oil. Departing from the lack of utilization of used oil waste and the absence of good tools to utilize used oil. On the other hand, when used as fuel, used oil does not produce complete combustion. This study uses the French design model. This study concluded that the designed stove (burner) has a large shape compared to the burner in general. The stove (burner) reaches a pressure of 3.5 bar with a temperature of 1127 °C. The flames produced by used oil are orange. Comparison of fuel results in data that LPG is 16 minutes faster than used oil in aluminum smelting. The highest flame length is 1.57 m at a variation of 3 bar air pressure and the lowest is 0.83 m at a pressure of 1 bar. There is an influence of pressure variations on the combustion temperature with a minimum and maximum temperature reaching the highest point with a pressure of 2.5 bar with a temperature of 118 °C and 994 °C while the lowest point is at a minimum and maximum temperature at a pressure of 1 bar with a temperature of 80.4 ° C and 662 °C at 0.5 bar pressure. Fuel consumption time with a distance variation of 2200 km produces a fairly short time of 12 minutes 25 seconds. While the consumption time obtained from the variation of the distance of 1800 km is 17 minutes 11 seconds.